1993
DOI: 10.1093/ajcp/99.3.238
|View full text |Cite
|
Sign up to set email alerts
|

Multicentricity in Breast Cancer: A Study of 366 Cases

Abstract: A total of 366 consecutive modified radical mastectomy specimens were studied for determination of multicentricity. The authors found that 187 samples (49.1%) were multicentric. Ten specimens contained in situ carcinoma without an infiltrating component; eight of them were multicentric. Multicentricity was correlated with various laboratory and clinical features, including patient age, tumor size, histologic type of breast cancer, tumor grade, presence and values of estrogen and progesterone receptors, the amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
1
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 0 publications
0
20
1
3
Order By: Relevance
“…It is likely that additional malignant disease also occurred in the non-MRI group. This assumption is supported by studies that reported more extensive disease in diverse groups of breast tumors [7,[32][33][34][35]. Consequently, a considerable part of undetected multi-focal tumor may be controlled by adjuvant treatment such as radiotherapy.…”
Section: Discussionmentioning
confidence: 77%
“…It is likely that additional malignant disease also occurred in the non-MRI group. This assumption is supported by studies that reported more extensive disease in diverse groups of breast tumors [7,[32][33][34][35]. Consequently, a considerable part of undetected multi-focal tumor may be controlled by adjuvant treatment such as radiotherapy.…”
Section: Discussionmentioning
confidence: 77%
“…The rate of multifocality and multicentricity varies widely from 11% to 57%. [1][2][3][4] If these additional foci can be identified preoperatively, the planned surgical management can be altered. Unfortunately, mammograms and ultrasonograms are not sensitive enough to detect some of these synchronous lesions.…”
mentioning
confidence: 99%
“…Breast cancer patients not rarely present multiple tumours (Lesser et al, 1982;Anastassiades et al, 1993;Vaidya et al, 1996). The increased emphasis in recent years on breast-sparing surgical treatment (Holland et al, 1985;Fisher, 1992;Connolly et al, 1995) has made it more clinically important to know whether multiple, ipsilateral breast carcinomas represent several primary tumours (multicentricity) or intramammary dissemination of a single carcinomatous process (multifocality).…”
mentioning
confidence: 99%